Isobutene / tert-butyl alcohol selective oxidation catalyst, and preparation method and application thereof
By using an imine compound containing a C=N double bond and a Schiff base ligand in the catalyst precipitation process, combined with a low-boiling-point pore-expanding agent, the problem of uneven metal ion distribution in the preparation of Mo-Bi-O catalysts was solved, and a highly efficient selective oxidation reaction of isobutylene/tert-butanol was achieved.
Patent Information
- Application Number
- CN202310119115.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-01
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2043-02-01
AI Technical Summary
Existing Mo-Bi-O catalysts suffer from uneven metal ion distribution during preparation, making it difficult to form uniform nanostructures and affecting catalyst performance.
In the catalyst precipitation process, metal ions are combined with imine compounds containing C=N double bonds, and easily decomposed low-boiling-point pore-expanding agents are used to separate and form uniform catalyst particles under mild conditions. The composition of metal ions is controlled by Schiff base ligands.
The catalyst significantly improved the feed conversion rate and target product selectivity of the selective oxidation reaction of isobutylene/tert-butanol.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of catalyst synthesis technology, specifically relating to a catalyst for improving the selective oxidation of isobutylene / tert-butanol in a fixed-bed reactor, its preparation method, and its application. Background Technology
[0002] Molybdenum-bismuth composite metal oxides (Mo-Bi-O) are most widely used in the selective oxidation of isobutylene / tert-butanol to methacrolein / methacrylic acid (unsaturated aldehyde / acid). The general preparation process for this type of catalyst is as follows: molybdenum, iron, cobalt, alkali metals, and other additives are added to a mother liquor system to form a multi-component mixture. The solvent (usually water) is removed from this system, and the resulting solid precipitate is calcined at high temperature to obtain catalyst matrix powder. The catalyst matrix powder is granulated to form particles of a certain size, and further shaped to obtain a molded body with a specific shape.
[0003] For multi-component composite metal oxide catalysts, achieving uniform dispersion of metal ions within the oxide structure and forming uniformly sized nanostructures has always been a challenge in their preparation. Current Mo-Bi-O catalysts are generally prepared using a co-precipitation method. During precipitation, the presence of multiple metals in the system, and the varying Ksp values of these metals, significantly influence the precipitation sequence and final precipitation effect. Some ions do not precipitate but dissolve in the system, forming uneven salts during solvent extraction, thus affecting their distribution in the final catalyst. Patent CN114425355A addresses the preparation of Mo-Bi-O catalysts by using acrylamide free radical polymerization to link polymer chains into a three-dimensional network ligand. This network ligand binds metal ions in solution, resulting in a uniform distribution of metal ions within the precursor's three-dimensional space. However, this method requires a larger amount of polymer monomer, increasing energy consumption and process complexity in subsequent organic matter treatment. Patent CN112675866A utilizes a microwave hydrothermal synthesis method to synthesize a composite metal oxide catalyst for isobutylene oxidation systems. An organic macromolecular pore-expanding agent is added during the solution precipitation process. However, this macromolecular pore-expanding agent cannot actually affect the precipitation process of metal ions or ensure particle uniformity; its effect during precipitation is not significant. Furthermore, since the catalyst itself experiences a weight loss rate of over 30% during subsequent high-temperature calcination, the pore-expanding agent is removed along with the catalyst bulk components during calcination, failing to increase the pore size. Summary of the Invention
[0004] To solve the problems existing in the prior art, the present invention provides a catalyst for the selective oxidation of isobutylene / tert-butanol via heterogeneous catalysis and a preparation method thereof. Compared with the catalysts in the prior art, a certain amount of metal ions is complexed with imine compounds containing C=N double bonds during the catalyst precipitation process, that is, part of the metal ions in the system are complexed with Schiff base ligands having multiple coordination sites, so as to control the uniformity of the metal ion composition, followed by continued thermal decomposition to obtain the composite oxide catalyst. During the thermal decomposition process of the catalyst, a certain amount of easily decomposable low-boiling point substance is simultaneously added as a pore-expanding agent, which is separated from the catalyst molded body under relatively mild conditions through a certain program control to form an improved molded catalyst. When the catalyst is used in the selective oxidation reaction of isobutylene / tert-butanol, it features high raw material conversion rate, and high selectivity and high yield of the generated target product.
[0005] One of the objectives of the present invention is to provide a catalyst for the selective oxidation of isobutylene / tert-butanol, comprising an active metal component and an auxiliary metal component, wherein the active metal component includes Mo, Bi, Fe and Co, and the auxiliary metal component includes at least one of rare earth metals, transition metals, alkali metals and alkaline earth metals. The general formula of the catalyst is:
[0006] Mo a Bi b Fe c Co d M I e M II f M III g M IV h O x ,
[0007] wherein, M I is a rare earth metal, M II is a transition metal, M III is an alkali metal, M IV is an alkaline earth metal, a=12, 0<b<3.5, 0<c<3, 0<d<8, 0≤e<1, 0≤f<2, 0<g≤2, 0<h≤2, and x is the number of oxygen atoms required in the composite oxide forming the catalytically active substance to satisfy the valence balance requirement of other non-oxygen elements;
[0008] Preferably, M I is selected from at least one of La, Ce, Pr, Nd, Er and Yb, M II is selected from at least one of Mn and Ni, M III is selected from at least one of K, Rb and Cs, M IV is selected from at least one of Mg and Ca.
[0009] The isobutylene / tert-butanol selective oxidation catalyst provided by the present invention is obtained by reacting and treating an active metal compound and a ligand compound containing an auxiliary metal compound, wherein the ligand in the ligand compound containing the auxiliary metal compound is a Schiff base ligand formed by the condensation of 1,3-propanediamine and 2-hydroxy-3-methoxybenzaldehyde.
[0010] A second objective of this invention is to provide a method for preparing the isobutylene / tert-butanol selective oxidation catalyst, comprising: mixing and reacting an active metal compound and a ligand compound containing an auxiliary metal compound, activating the mixture, and performing a pore-expanding treatment to obtain the catalyst. Preferably, the preparation method specifically includes the following steps:
[0011] S1. An active metal compound and a ligand compound containing an auxiliary metal compound are added to an acidic liquid medium and mixed to react. After removing the liquid medium, a catalyst precursor is obtained.
[0012] S2. The catalyst precursor obtained in step S1 is activated by heating to obtain catalyst powder.
[0013] S3. Add a pore-expanding agent to the catalyst powder obtained in step S2, mix evenly, and then press into shape.
[0014] S4. After heating to remove the pore-expanding agent, the isobutylene / tert-butanol selective oxidation catalyst is obtained.
[0015] According to some embodiments of the present invention:
[0016] The active metal compound is selected from at least one of active metal oxides, ammonium salts, nitrates, carbonates, bicarbonates, sulfates, halides, oxalates, acetates, phosphates, hydrogen phosphates, and complexes, preferably from at least one of active metal ammonium salts, nitrates, oxalates, acetates, and complexes.
[0017] The auxiliary metal compound is selected from at least one of the following: oxides, ammonium salts, nitrates, carbonates, bicarbonates, sulfates, halides, oxalates, acetates, phosphates, hydrogen phosphates, and complexes of the auxiliary metal; preferably, at least one of the following: ammonium salts, nitrates, oxalates, and acetates of the auxiliary metal.
[0018] The ligand compound containing the auxiliary metal compound is a complex formed by the auxiliary metal compound, 1,3-propanediamine and 2-hydroxy-3-methoxybenzaldehyde, wherein the molar ratio of the auxiliary metal compound, 1,3-propanediamine and 2-hydroxy-3-methoxybenzaldehyde is 1:(1-3):(1-4), preferably 1:(1-2):(1-3).
[0019] According to some embodiments of the present invention, the acidic liquid medium in step S1 is not particularly limited. Depending on the catalyst reaction system, any solvent commonly used in the art can be selected. Preferably, the acidic liquid medium is an aqueous solvent with a certain acid strength, i.e., a solvent containing water or a liquid mixture containing one or more other solvents miscible with water (such as polar organic solvents, particularly alcohols). For catalysts for the oxidation of isobutylene / tert-butanol to methacrolein and / or methacrylic acid, the solvent is selected from at least one of water and organic solvents, preferably at least one of water and alcohols.
[0020] According to some embodiments of the present invention, the acid in the acidic liquid medium is selected from at least one of inorganic acids and organic acids. The inorganic acid is selected from at least one of nitric acid, sulfuric acid, hydrochloric acid, and phosphoric acid, preferably from at least one of nitric acid and phosphoric acid. The organic acid is selected from at least one of hydroxycarboxylic acids, monocarboxylic acids, dicarboxylic acids, and tricarboxylic acids, preferably from at least one of acetic acid, citric acid, oxalic acid, lactic acid, malonic acid, succinic acid, maleic acid, fumaric acid, malic acid, adipic acid, tartaric acid, caffeic acid, and ferulic acid. According to embodiments of the present invention, the acid is particularly preferably an inorganic acid, an inorganic acid, or a combination of acetic acid and a chelated organic acid, i.e., a metal that can stabilize the precursor compound of the catalytically active component under certain acidic conditions by means of more than one coordinate bond in the organic acid. It is especially preferred to be at least one of α-hydroxycarboxylic acids, dicarboxylic acids, and tricarboxylic acids, such as at least one of acetic acid, citric acid, tartaric acid, maleic acid, succinic acid, adipic acid, and oxalic acid.
[0021] According to some embodiments of the present invention, the concentration of acid in the acidic liquid medium is not particularly limited. Preferably, the mass percentage of acid in the acidic liquid medium is 2-15%, and more preferably 5-15%.
[0022] According to some embodiments of the present invention, the pore-expanding agent is selected from at least one of diacids and ammonium salts having 2 to 4 carbon atoms, preferably from at least one of oxalic acid, ammonium oxalate, ammonium acetate, ammonium carbonate, ammonium bicarbonate, and ammonium bioxalate. The present invention preferably uses a pore-expanding agent that can be removed at low temperatures. Firstly, its decomposition temperature is low, allowing removal at temperatures below 200°C, thus avoiding changes in the active crystalline phase of the oxide due to high temperatures. Secondly, the pore-expanding agent can form a reducing atmosphere NH3 during decomposition, which can significantly improve the performance of the catalyst. When the pore-expanding agent is mixed with the catalyst powder, it needs to be granulated into particles of a certain size beforehand. The pore-expanding agent selected in the present invention has a particle size of less than 20 mesh, wherein the weight ratio of particles between 20 and 40 mesh is 30-60%, and the weight ratio of particles >40 mesh is 40-70%.
[0023] In step S3, the mass ratio of the pore-expanding agent to the catalyst powder is (2-15):(85-98), preferably (4-10):(90-96), and more preferably (4-8):(92-96); the particle size of the catalyst powder obtained in step 2 is less than 20 mesh, wherein the content of particles between 20 and 40 mesh is 30-60 wt%, and the content of particles >40 mesh is 40-70 wt%.
[0024] In step S3, a lubricant is also added, wherein the lubricant is selected from at least one of graphite and hydroxysilicate, and the mass ratio of the lubricant to the pore-expanding agent is (3-6):(2-10), preferably (4-6):(6-10).
[0025] After the catalyst powder and the pore expander are mixed evenly, the pore expander is removed. The removal temperature is crucial for the catalyst. It is necessary to control the appropriate removal temperature to remove the pore expander at a lower temperature to avoid adverse effects on the catalyst structure and performance. The pore expander removal temperature selected in this invention is 100-250℃.
[0026] According to some embodiments of the present invention, step S1 includes:
[0027] S1-1. Add a portion of the active metal compound to an acidic liquid medium and heat.
[0028] S1-2, Add the remaining active metal compound and continue heating to obtain a reaction system containing a precipitate;
[0029] S1-3. Add a ligand compound containing a auxiliary metal compound to the reaction system;
[0030] S1-4. After solid-liquid separation, the obtained precipitate is dried to obtain the catalyst precursor.
[0031] In step S1-1, the heating temperature is 40-80℃, preferably 50-70℃; the heating time is 0.1-5h, preferably 3-5h.
[0032] The heating temperature in step S1-2 is 40-80℃, preferably 50-70℃; the heating time is 3-24h, preferably 3-16h.
[0033] In steps S1-3, the ligand compound containing the auxiliary metal compound can be obtained by directly adding the complex separated after the ligand reacts with the auxiliary metal, or by directly adding the system after the ligand reacts with the auxiliary metal; wherein, the preparation method of the ligand compound containing the auxiliary metal compound includes: firstly, condensing 1,3-propanediamine and 2-hydroxy-3-methoxybenzaldehyde to obtain the ligand, and then adding the auxiliary metal compound to obtain the ligand compound containing the auxiliary metal compound; preferably, the condensation reaction conditions are 40-80℃ for 3-6 hours;
[0034] There is no particular limitation on the order of adding the ligand compound containing the auxiliary metal compound in steps S1-3. The dispersion system containing the ligand compound containing the auxiliary metal compound can be directly added to other dispersion systems in steps S1-2, or the dispersion system containing the ligand compound containing the auxiliary metal compound can be directly added to the formed mixed reaction solution, or they can be added at the same time.
[0035] The operation process in steps S1-4 is not particularly limited. For example, the reaction solution containing the precipitate can be spray-dried to obtain the precipitate, or the solid precipitate can be obtained by evaporating the solvent in the reaction solution. Finally, the catalyst precursor is dried. The drying conditions are 80-150°C for 6-24 hours, preferably 120-150°C for 12-24 hours.
[0036] According to some embodiments of the present invention:
[0037] The heating activation operation in step S2 can adopt the heating activation operation method commonly used in the art, preferably the following specific operation: heat up to 240-260°C at a rate of 1-4°C / min, hold at this temperature for 0.5-2 hours, continue to heat up to 260-280°C at a rate of 1-2°C / min, hold at this temperature for 0.5-1 hours, continue to heat up to 280-300°C at a rate of 1-2°C / min, hold at this temperature for 0-0.5 hours, and finally heat up to 300-350°C at a rate of 1-2°C / min, hold at this temperature for 1-3 hours;
[0038] The specific operation of step S4 is as follows: the molded body is placed in an activation device, heated to 100-250°C at a rate of 0.5-2°C / min, and held at this temperature for 3-6 hours. Then, the temperature is further increased to 450-520°C at a rate of 1-3°C / min and held at this temperature for 2-5 hours. Subsequently, the temperature is cooled to room temperature to obtain the catalyst.
[0039] A third objective of this invention is to provide the aforementioned catalyst, or a catalyst obtained by the aforementioned preparation method. Based on the characteristics of oxidation reactions, the catalyst in the reaction bed must have sufficient bulk density to withstand the reaction pressure while simultaneously forming a certain porosity to ensure effective contact of the gas flow. According to some embodiments of the invention, the bulk density of the catalyst is 0.5–1.8 g / cm³. 3 Preferably, it is 0.6–1.5 g / cm³. 3 More preferably, it is 0.7–1.2 g / cm³. 3 Changes in specific surface area have a significant impact on catalyst activity, improving feed conversion rate, and enhancing the selectivity of target products. According to some embodiments of the present invention, the specific surface area of the catalyst is 5–50 m². 2 / g, preferably 10-40m 2 / g, more preferably 10-30m 2 / g. Within this range, the catalyst surface facilitates effective contact between reactant molecules and the catalyst active sites, while also inhibiting further peroxidation of the target product, thereby improving catalyst activity and product selectivity.
[0040] The fourth objective of this invention is to provide the above-mentioned selective oxidation catalyst for isobutylene / tert-butanol, and its application in the oxidation reaction of isobutylene / tert-butanol to produce methacrolein / acid.
[0041] The fifth objective of this invention is to provide a method for producing methacrolein / acid by the oxidation reaction of isobutylene / tert-butanol, comprising the step of contacting isobutylene / tert-butanol with the catalyst to carry out the oxidation reaction.
[0042] According to some embodiments of the present invention, the conditions for the oxidation reaction include:
[0043] The reaction temperature is 300–400℃;
[0044] The reaction time is 1–48 hours;
[0045] The total volumetric space velocity of the raw material is 500–3000 h⁻¹. -1 Preferably 800-2000h -1 ,
[0046] The pressure is 0.01–0.2 MPa;
[0047] The molar ratio of isobutylene:oxygen:water in the raw material is 1:(1-5):(2-6), or the molar ratio of tert-butanol:oxygen:water in the raw material is 1:(1-5):(1-5).
[0048] The catalyst powder in this invention is formed by activating the catalyst precursor through step S2 and then calcining it at a temperature below 300°C for a certain period of time. Because the catalyst precursor undergoes a significant phase transition and weight loss during the heating process to 300°C, with a weight loss rate >30% (weight loss rate = weight reduction after heat treatment / weight before heat treatment × 100%), the catalyst precursor is mixed with a pore-expanding agent after significant weight loss and then further activated by heating. This ensures a relatively uniform activated state of the catalyst composition. The final catalyst profile can be directly used in the selective oxidation of isobutylene / tert-butanol to methacrolein.
[0049] The beneficial effects of this invention are as follows: By using the catalyst provided by this invention, a certain amount of metal ions are combined with imine compounds with C=N double bonds during the catalyst precipitation process to control the uniformity of the metal ion composition, forming uniform and fine particles, thus ensuring more active catalyst particles; at the same time, the use of low-temperature pore expander can not only form channels on the catalyst body, but also form a reducing atmosphere during the activation process, reducing the high-temperature heat treatment process in the traditional pore expander treatment process, which reduces the treatment time, prevents phase changes, and improves catalyst performance.
[0050] The catalyst prepared using this invention is used in a fixed-bed reactor for the catalytic gas-phase selective oxidation of isobutylene / tert-butanol to methacrolein, at a reaction temperature of 300–400 °C, an isobutylene / tert-butanol ratio of 3–10 vol%, and a space velocity of 800–2000 h⁻¹. -1 Under conditions of 3–10 v% isobutylene / tert-butanol and a pressure of 0.01–0.2 MPa, the conversion rate of isobutylene / tert-butanol is 96.0–99.0%, and the selectivity of methacrolein reaches 86.0–89.8%. Detailed Implementation
[0051] The present invention will now be described in detail with reference to specific embodiments. It should be noted that the following embodiments are only used to further illustrate the present invention and should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the content of the present invention are still within the scope of protection of the present invention.
[0052] The testing instruments and conditions used in this embodiment are as follows:
[0053] Specific surface area was determined using an ASAP-2020 fully automated specific surface area and pore size analyzer from Quantachrome, USA. Catalyst bulk density was determined using a tap density meter.
[0054] Catalyst performance evaluation experiments were conducted in a single-tube reactor. The reactor tube was 4 m long with an effective length of 3.6 m and an inner diameter of 25 mm, housing a 6 mm outer diameter thermocouple. The catalyst loading was 1200 mL, with a loading height of 3.3–3.6 m. Air and isobutylene were metered by mass flow meters, while tert-butanol was metered by a precision metering pump before entering the reaction tube. A branch line was added at the inlet for gas chromatography analysis of the feed gas composition. The reaction gas underwent selective oxidation to generate the target product under the action of the activated catalyst, and the tail gas composition was analyzed by adding a branch line at the tail gas outlet. Chromatographic analysis was performed using an Agilent 7890b gas chromatograph. All data used in the following discussion are based on carbon balance values between 98% and 102%.
[0055] According to the present invention, the contact conditions can be selected within a wide range. However, in order to further improve the selectivity of methacrolein and methacrylic acid, the contact conditions preferably include: a temperature of 300–400°C, a pressure of 0.01–0.2 MPa, a reaction time of 1–48 h, and a total volume hourly space velocity (VHSV) of 500–3000 h⁻¹. -1 Preferably 800-2000h -1 The molar ratio of isobutylene:oxygen:water in the raw materials is 1:(1-5):(2-6). Alternatively, the contact conditions include: a temperature of 300-400℃, a pressure of 0.01-0.2MPa, a reaction time of 1-48h, and a space velocity of 500-3000h⁻¹. -1 Preferably 800-2000h -1 The molar ratio of tert-butanol:oxygen:water in the raw materials is 1:(1~5):(1~5).
[0056] The calculations for the conversion rate of reactants and the selectivity of products during the reaction process are as follows:
[0057]
[0058]
[0059]
[0060] Unless otherwise specified, the raw materials used in the examples and comparative examples are all disclosed in the prior art, such as those that can be directly purchased or prepared according to the preparation methods disclosed in the prior art.
[0061]
Preparation Example 1
[0062] Ligand L was prepared by condensation reaction of 1,3-propanediamine and 2-hydroxy-3-methoxybenzaldehyde. 74.4 g (480 mmol) of 2-hydroxy-3-methoxybenzaldehyde was weighed into a 3000 mL round-bottom flask and dissolved in 1200 mL of ethanol. The solution was yellow. 240 mL of an ethanol solution containing 37.8 g (240 mmol) of 1,3-propanediamine was added to the round-bottom flask through a constant-pressure funnel. The mixture was stirred in a 60 °C water bath for 4 h to obtain a deep yellow solution. After evaporating 1000-1200 mL of ethanol solvent by rotary evaporation, the solution was filtered, washed with ethanol, and dried under vacuum to obtain 74 g of yellow crystals, labeled as ligand L.
[0063]
Example 1
[0064] 1000g of ammonium heptamolybdate was dissolved in 2000g of deionized water at 60℃ to obtain solution A; 229g of bismuth nitrate, 381g of ferric nitrate, 682g of cobalt acetate, 60.6g of magnesium nitrate, and 37.0g of cesium nitrate were dissolved in 1840g of 5% dilute nitric acid aqueous solution at 60℃ to obtain solution B; 64.6g of ligand L was weighed and dissolved in 440mL of ethanol, stirred at 60℃ to dissolve, and 400mL of a mixed solution containing 46g of manganese acetate tetrahydrate (ethanol:water = 1:1) was slowly added dropwise, stirred for 2h, and then a solution containing 41g of lanthanum nitrate hexahydrate in acetonitrile was added dropwise to prepare dispersion system C; solutions B and dispersion system C were added dropwise to solution A respectively. The slurry was stirred and matured at 60℃ for 4h. The obtained slurry was spray-dried at 140℃ to remove the solvent components. The resulting solid was heated to 250℃ at a rate of 2℃ / min and held at 250℃ for 2 hours. The temperature was then increased to 260℃ at a rate of 1℃ / min and held at this temperature for 0.5 hours. Finally, the temperature was increased to 300℃ at a rate of 2℃ / min and held at this temperature for 3 hours, yielding 1696g of brown solid powder. This powder was granulated to particles smaller than 20 mesh, with 45% by weight of particles between 20 and 40 mesh. 70.7g of graphite and 147.5g of oxalic acid with a particle size smaller than 20 mesh were added, with a mass ratio of oxalic acid to catalyst powder of 8:92 and a mass ratio of graphite to catalyst powder of 4:96. After thorough mixing, the mixture was pressed into hollow cylindrical catalysts with an outer diameter of 5.5mm, a height of 4mm, and an inner diameter of 2.5mm. The catalyst prototype was heated to 100°C at a rate of 2°C / min and held at this temperature for 6 hours to remove the pore-expanding agent. The temperature was then further increased to 500°C at a rate of 3°C / min and held at this temperature for 2 hours. Finally, the temperature was cooled to room temperature to obtain the activated catalyst. The catalyst bulk density was 1.07 g / cm³. 3 Its specific surface area is 14.3 m². 2 / g, with a lateral impact strength of 36N. The catalyst composition is shown in Table 1. The obtained catalyst was loaded into a single-tube fixed-bed reactor and evaluated; the catalytic performance is shown in Table 2.
[0065]
Example 2
[0066] 1000g of ammonium heptamolybdate was dissolved in 2000g of deionized water at 60℃ to obtain solution A; 344g of bismuth nitrate, 190g of ferric nitrate, 586g of cobalt acetate, 120g of magnesium nitrate, and 54g of cesium nitrate were dissolved in 1840g of 5% dilute nitric acid aqueous solution at 60℃ to obtain solution B; 64.6g of ligand L was weighed and dissolved in 440mL of ethanol, stirred at 60℃ to dissolve, and 400mL of a mixed solution containing 23g of manganese acetate tetrahydrate (ethanol:water = 1:1) was slowly added dropwise, stirred for 2h, and then a solution containing 61.4g of lanthanum nitrate hexahydrate in acetonitrile was added dropwise to obtain dispersion system C; solution B and dispersion system C were added dropwise to solution A respectively. The slurry was stirred and matured at 60℃ for 4h. The obtained slurry was spray-dried at 140℃ to remove the solvent components. The resulting solid was heated to 250℃ at a rate of 3℃ / min and held at 250℃ for 1 hour. The temperature was then increased to 260℃ at a rate of 0.5℃ / min and held at this temperature for 1 hour. Finally, the temperature was increased to 300℃ at a rate of 2℃ / min and held at this temperature for 3 hours, yielding 1703g of brown solid powder. This powder was granulated to particles smaller than 20 mesh, with 35% by weight of particles between 20 and 40 mesh. 71.0g of graphite and 189.2g of ammonium oxalate (particles smaller than 20 mesh) were added, with a mass ratio of ammonium oxalate to catalyst powder of 10:90 and a mass ratio of graphite to catalyst powder of 4:96. After thorough mixing, the mixture was pressed into hollow cylindrical catalysts with an outer diameter of 5.5mm, a height of 4mm, and an inner diameter of 2.5mm. The catalyst prototyping was heated to 250°C at a rate of 1°C / min and held at this temperature for 3 hours to remove the pore-expanding agent. Then, the temperature was further increased to 500°C at a rate of 3°C / min and held at this temperature for 3 hours. Finally, the temperature was cooled to room temperature to obtain the activated catalyst. The catalyst bulk density was 1.04 g / cm³. 3 Its specific surface area is 15.0 m². 2 / g, with a lateral impact strength of 34N. The catalyst composition is shown in Table 1. The obtained catalyst was loaded into a single-tube fixed-bed reactor and evaluated; the catalytic performance is shown in Table 2.
[0067]
Example 3
[0068] 1000g of ammonium heptamolybdate was dissolved in 2000g of deionized water at 60℃ to obtain solution A; 460g of bismuth nitrate, 554g of ferric nitrate, 242g of cobalt acetate, 182g of magnesium nitrate, and 82g of cesium nitrate were dissolved in 1840g of 5% dilute nitric acid aqueous solution at 60℃ to obtain solution B; 193.8g of ligand L was weighed and dissolved in 440mL of ethanol, stirred at 60℃ to dissolve, and 400mL of a mixed solution containing 69.4g of manganese acetate tetrahydrate (ethanol:water = 1:1) was slowly added dropwise, stirred for 2h, and then a solution containing 20.6g of lanthanum nitrate hexahydrate in acetonitrile was added dropwise to prepare dispersion system C; solution B and dispersion system C were added dropwise to solution A respectively. The slurry was stirred and matured at 60℃ for 4h. The obtained slurry was subjected to vacuum distillation in a rotary evaporator at 140℃ to remove the solvent components. The resulting solid was heated to 250℃ at a rate of 2℃ / min and held at 250℃ for 2 hours. The temperature was then increased to 260℃ at a rate of 0.5℃ / min and held at this temperature for 1 hour. Finally, the temperature was increased to 300℃ at a rate of 2℃ / min and held at this temperature for 3 hours, yielding 1710g of brown solid powder. This powder was granulated to particles smaller than 20 mesh, with 30% by weight of particles between 20 and 40 mesh. 71.3g of graphite and 301.8g of ammonium acetate with a particle size smaller than 20 mesh were added, with a mass ratio of ammonium acetate to catalyst powder of 15:85 and a mass ratio of graphite to catalyst powder of 4:96. After thorough mixing, the mixture was pressed into hollow cylindrical catalysts with an outer diameter of 5.5mm, a height of 4mm, and an inner diameter of 2.5mm. The catalyst prototyping was heated to 200°C at a rate of 1°C / min and held at this temperature for 5 hours to remove the pore-expanding agent. Then, the temperature was further increased to 500°C at a rate of 3°C / min and held at this temperature for 3 hours. Finally, the temperature was cooled to room temperature to obtain the activated catalyst. The catalyst bulk density was 0.97 g / cm³. 3 Its specific surface area is 16.1 m². 2 / g, with a lateral impact strength of 29N. The catalyst composition is shown in Table 1. The obtained catalyst was loaded into a single-tube fixed-bed reactor and evaluated; the catalytic performance is shown in Table 2.
[0069]
Example 4
[0070] 1000g of ammonium heptamolybdate was dissolved in 2000g of deionized water at 60℃ to obtain solution A; 688g of bismuth nitrate, 286g of ferric nitrate, 406g of cobalt acetate, 194g of magnesium nitrate, and 128g of rubidium nitrate were dissolved in 1840g of 5% dilute nitric acid aqueous solution at 60℃ to obtain solution B; 258.2g of ligand L was weighed and dissolved in 440mL of ethanol, stirred at 60℃ to dissolve, and 400mL of acetonitrile solution containing 188g of nickel acetate tetrahydrate was slowly added dropwise, stirred for 2h, and then acetonitrile solution containing 20.6g of lanthanum nitrate hexahydrate was added dropwise to obtain dispersion system C; solution B and dispersion system C were added dropwise to solution A respectively. The slurry was stirred and matured at 60℃ for 4h. The obtained slurry was subjected to vacuum distillation in a rotary evaporator at 140℃ to remove the solvent components. The resulting solid was heated to 250℃ at a rate of 2℃ / min and held at 250℃ for 2 hours. The temperature was then increased to 260℃ at a rate of 0.5℃ / min and held at this temperature for 1 hour. Finally, the temperature was increased to 300℃ at a rate of 2℃ / min and held at this temperature for 3 hours, yielding 1711g of brown solid powder. This powder was granulated to particles smaller than 20 mesh, with 30% by weight of particles between 20 and 40 mesh. 71.3g of graphite and 90g of ammonium carbonate with a particle size smaller than 20 mesh were added, with a mass ratio of ammonium carbonate to catalyst powder of 5:95 and a mass ratio of graphite to catalyst powder of 4:96. After thorough mixing, the mixture was pressed into hollow cylindrical catalysts with an outer diameter of 5.5mm, a height of 4mm, and an inner diameter of 2.5mm. The catalyst prototyping was heated to 200°C at a rate of 1°C / min and held at this temperature for 3 hours to remove the pore-expanding agent. Then, the temperature was further increased to 500°C at a rate of 2°C / min and held at this temperature for 3 hours. Finally, the temperature was cooled to room temperature to obtain the activated catalyst. The catalyst bulk density was 1.13 g / cm³. 3 Its specific surface area is 13.2 m². 2 / g, with a lateral impact strength of 42N. The catalyst composition is shown in Table 1. The obtained catalyst was loaded into a single-tube fixed-bed reactor and evaluated; the catalytic performance is shown in Table 2.
[0071]
Example 5
[0072] 1000g of ammonium heptamolybdate was dissolved in 2000g of deionized water at 60℃ to obtain solution A; 526g of bismuth nitrate, 552g of ferric nitrate, 302g of cobalt acetate, 108g of magnesium nitrate, and 91g of rubidium nitrate were dissolved in 1840g of 5% dilute nitric acid aqueous solution at 60℃ to obtain solution B; 81.0g of ligand L was weighed and dissolved in 440mL of ethanol, stirred at 60℃ to dissolve, and 400mL of acetonitrile solution containing 59g of nickel acetate tetrahydrate was slowly added dropwise, stirred for 2h, and then acetonitrile solution containing 40.3g of cerium nitrate hexahydrate was added dropwise to obtain dispersion system C; solution B and dispersion system C were added dropwise to solution A respectively. The slurry was stirred and matured at 60℃ for 4h. The obtained slurry was subjected to vacuum distillation in a rotary evaporator at 140℃ to remove the solvent components. The resulting solid was heated to 250℃ at a rate of 2℃ / min and held at 250℃ for 2 hours. The temperature was then increased to 260℃ at a rate of 0.5℃ / min and held at this temperature for 1 hour. Finally, the temperature was increased to 300℃ at a rate of 2℃ / min and held at this temperature for 3 hours, yielding 1682g of brown solid powder. This powder was granulated to particles smaller than 20 mesh, with 60% by weight of particles between 20-40 mesh. 70.1g of graphite and 34.3g of ammonium bicarbonate with a particle size between 20-40 mesh were added, with a mass ratio of ammonium bicarbonate to catalyst powder of 2:98 and a mass ratio of graphite to catalyst powder of 4:96. After thorough mixing, the mixture was pressed into hollow cylindrical catalysts with an outer diameter of 5.5mm, a height of 4mm, and an inner diameter of 2.5mm. The catalyst prototyping was heated to 200°C at a rate of 1°C / min and held at this temperature for 3 hours to remove the pore-expanding agent. Then, the temperature was further increased to 500°C at a rate of 2°C / min and held at this temperature for 3 hours. Finally, the temperature was cooled to room temperature to obtain the activated catalyst. The catalyst bulk density was 1.19 g / cm³. 3 Its specific surface area is 11.1 m². 2 / g, with a lateral impact strength of 46N. The catalyst composition is shown in Table 1. The obtained catalyst was loaded into a single-tube fixed-bed reactor and evaluated; the catalytic performance is shown in Table 2.
[0073]
Example 6
[0074] 1000g of ammonium heptamolybdate was dissolved in 2000g of deionized water at 60℃ to obtain solution A; 778g of bismuth nitrate, 382g of ferric nitrate, 164g of cobalt acetate, 222g of calcium nitrate, and 38g of potassium nitrate were dissolved in 1840g of 5% dilute nitric acid aqueous solution at 60℃ to obtain solution B; 193.8g of ligand L was weighed and dissolved in 440mL of ethanol, stirred at 60℃ to dissolve, and 400mL of a mixed solution containing 69.4g of manganese acetate tetrahydrate (ethanol:water = 1:1) was slowly added dropwise, stirred for 2h, and then a solution containing 40.3g of cerium nitrate hexahydrate in acetonitrile was added dropwise to prepare dispersion system C; solution B and dispersion system C were added dropwise to solution A respectively. The slurry was stirred and matured at 60℃ for 4h. The obtained slurry was subjected to vacuum distillation in a rotary evaporator at 140℃ to remove the solvent components. The resulting solid was heated to 250℃ at a rate of 2℃ / min and held at 250℃ for 2 hours. The temperature was then increased to 260℃ at a rate of 0.5℃ / min and held at this temperature for 1 hour. Finally, the temperature was increased to 300℃ at a rate of 2℃ / min and held at this temperature for 3 hours, yielding 1701g of brown solid powder. This powder was granulated to particles smaller than 20 mesh, with 70% by weight of particles between 20-40 mesh. 70.9g of graphite and 189g of ammonium oxalate with a particle size between 20-40 mesh were added, with a mass ratio of ammonium oxalate to catalyst powder of 10:90 and a mass ratio of graphite to catalyst powder of 4:96. After thorough mixing, the mixture was pressed into hollow cylindrical catalysts with an outer diameter of 5.5mm, a height of 4mm, and an inner diameter of 2.5mm. The catalyst prototyping was heated to 200°C at a rate of 1°C / min and held at this temperature for 3 hours to remove the pore-expanding agent. Then, the temperature was further increased to 500°C at a rate of 2°C / min and held at this temperature for 3 hours. Finally, the temperature was cooled to room temperature to obtain the activated catalyst. The catalyst bulk density was 1.09 g / cm³. 3 Its specific surface area is 18.7 m². 2 / g, with a lateral impact strength of 31N. The catalyst composition is shown in Table 1. The obtained catalyst was loaded into a single-tube fixed-bed reactor for evaluation, and the catalytic performance is shown in Table 2.
[0075]
Example 7
[0076] 1000g of ammonium heptamolybdate was dissolved in 2000g of deionized water at 60℃ to obtain solution A; 230g of bismuth nitrate, 286g of ferric nitrate, 434g of cobalt acetate, 61g of calcium nitrate, and 94g of potassium nitrate were dissolved in 1840g of 5% dilute nitric acid aqueous solution at 60℃ to obtain solution B; 80.8g of ligand L was weighed and dissolved in 440mL of ethanol, stirred at 60℃ to dissolve, and 400mL of a mixed solution containing 57.5g of manganese acetate tetrahydrate (ethanol:water = 1:1) was slowly added dropwise, stirred for 2h, and then a solution containing 102.5g of lanthanum nitrate hexahydrate in acetonitrile was added dropwise to prepare dispersion system C; solution B and dispersion system C were added dropwise to solution A respectively. The slurry was stirred and matured at 60℃ for 4h. The obtained slurry was evaporated in an oven at 140℃ to remove the solvent components. The resulting solid was heated to 250℃ at a rate of 2℃ / min and held at 250℃ for 2 hours. The temperature was then increased to 260℃ at a rate of 0.5℃ / min and held at this temperature for 1 hour. Finally, the temperature was increased to 300℃ at a rate of 2℃ / min and held at this temperature for 3 hours, yielding 1714g of brown solid powder. This powder was granulated to particles smaller than 20 mesh, with 50% by weight of particles between 20-40 mesh. 71.4g of graphite and 149g of oxalic acid with a particle size between 20-40 mesh were added, with a mass ratio of oxalic acid to catalyst powder of 8:92 and a mass ratio of graphite to catalyst powder of 4:96. After thorough mixing, the mixture was pressed into hollow cylindrical catalysts with an outer diameter of 5.5mm, a height of 4mm, and an inner diameter of 2.5mm. The catalyst prototyping was heated to 250°C at a rate of 1°C / min and held at this temperature for 3 hours to remove the pore-expanding agent. Then, the temperature was further increased to 500°C at a rate of 2°C / min and held at this temperature for 3 hours. Finally, the temperature was cooled to room temperature to obtain the activated catalyst. The catalyst bulk density was 1.08 g / cm³. 3 Its specific surface area is 16.2 m². 2 / g, with a lateral impact strength of 34N. The catalyst composition is shown in Table 1. The obtained catalyst was loaded into a single-tube fixed-bed reactor and evaluated; the catalytic performance is shown in Table 2.
[0077]
Example 8
[0078] 1000g of ammonium heptamolybdate was dissolved in 2000g of deionized water at 60℃ to obtain solution A; 229g of bismuth nitrate, 381g of ferric nitrate, 586g of cobalt acetate, 120g of magnesium nitrate, and 37.0g of cesium nitrate were dissolved in 1840g of 5% dilute acetic acid aqueous solution at 60℃ to obtain solution B; 64.6g of ligand L was weighed and dissolved in 440mL of ethanol, stirred at 60℃ to dissolve, and 400mL of a mixed solution containing 46g of manganese acetate tetrahydrate (ethanol:water = 1:1) was slowly added dropwise, stirred for 2h, and then a solution containing 41g of lanthanum nitrate hexahydrate in acetonitrile was added dropwise to prepare dispersion system C; solutions B and dispersion system C were added dropwise to solution A respectively. The slurry was stirred and matured at 60℃ for 4h. The obtained slurry was spray-dried at 200℃ to remove the solvent components. The resulting solid was heated to 250℃ at a rate of 2℃ / min and held at 250℃ for 2 hours. The temperature was then increased to 260℃ at a rate of 1℃ / min and held at this temperature for 0.5 hours. Finally, the temperature was increased to 300℃ at a rate of 2℃ / min and held at this temperature for 3 hours, yielding 1648g of brown solid powder. This powder was granulated to particles smaller than 20 mesh, with 45% by weight of particles between 20 and 40 mesh. 68.7g of graphite and 124.0g of oxalic acid with a particle size smaller than 20 mesh were added, with a mass ratio of oxalic acid to catalyst powder of 7:93 and a mass ratio of graphite to catalyst powder of 4:96. After thorough mixing, the mixture was pressed into hollow cylindrical catalysts with an outer diameter of 5.5mm, a height of 4mm, and an inner diameter of 2.5mm. The catalyst prototype was heated to 100°C at a rate of 2°C / min and held at this temperature for 6 hours to remove the pore-expanding agent. The temperature was then further increased to 500°C at a rate of 3°C / min and held at this temperature for 2 hours. Finally, the temperature was cooled to room temperature to obtain the activated catalyst. The catalyst bulk density was 1.08 g / cm³. 3 Its specific surface area is 14.9 m². 2 / g, with a lateral impact strength of 35N. The catalyst composition is shown in Table 1. The obtained catalyst was loaded into a single-tube fixed-bed reactor for evaluation, and the catalytic performance is shown in Table 2.
[0079] Comparative Example 1
[0080] 1000g of ammonium heptamolybdate was dissolved in 2000g of deionized water at 60℃ to obtain solution A. 229g of bismuth nitrate, 381g of ferric nitrate, 682g of cobalt acetate, 60.6g of magnesium nitrate, 37.0g of cesium nitrate, 46g of manganese acetate tetrahydrate, and 41g of lanthanum nitrate hexahydrate were dissolved in 1840g of 5% dilute nitric acid aqueous solution at 60℃ to obtain dispersion system B. Dispersion system B was added dropwise to solution A. The slurry was stirred and matured at 60℃ for 4 hours. The solvent components in the resulting slurry were evaporated under spray drying conditions at 140℃. The resulting solid was heated to 250℃ at a rate of 2℃ / min and held at 250℃ for 2 hours. The temperature was then increased to 260℃ at a rate of 1℃ / min and held at this temperature for 0.5 hours. Finally, the temperature was increased to 300℃ at a rate of 2℃ / min and held at this temperature for 3 hours, yielding 1688g of brown solid powder. The catalyst was granulated to particles smaller than 20 mesh, with 45% by weight of particles between 20 and 40 mesh. 70.7 g of graphite and 147.5 g of oxalic acid (particles smaller than 20 mesh) were added, with an oxalic acid to catalyst powder mass ratio of 8:92 and a graphite to catalyst powder mass ratio of 4:96. After thorough mixing, the mixture was pressed into hollow cylindrical catalyst bodies with an outer diameter of 5.5 mm, a height of 4 mm, and an inner diameter of 2.5 mm. The catalyst body was heated to 200 °C at a rate of 2 °C / min and held at this temperature for 5 h. Then, the temperature was increased to 500 °C at a rate of 3 °C / min and held at this temperature for 2 h. Finally, the temperature was cooled to room temperature to obtain the activated catalyst. The catalyst bulk density was 1.07 g / cm³. 3 Its specific surface area is 9.7 m². 2 / g, with a lateral impact strength of 36N. The catalyst composition is shown in Table 1. The obtained catalyst was loaded into a single-tube fixed-bed reactor and evaluated; the catalytic performance is shown in Table 2.
[0081] Comparative Example 2
[0082] The catalyst slurry preparation process and calcination process at 300℃ were the same as in Example 2. After calcination, 1701g of brown solid powder was obtained. This powder was granulated into particles smaller than 20 mesh, with 35% by weight of particles between 20-40 mesh, and only 71.0g of graphite was added. After uniform mixing, it was pressed into hollow cylindrical catalyst bodies with an outer diameter of 5.5mm, a height of 4mm, and an inner diameter of 2.5mm. The catalyst body was heated to 200℃ at a rate of 1℃ / min and held at this temperature for 3 hours. Then, the temperature was further increased to 500℃ at a rate of 3℃ / min and held at this temperature for 3 hours. Finally, it was cooled to room temperature to obtain the activated catalyst. The catalyst bulk density was 1.04g / cm³. 3 Its specific surface area is 10.1 m². 2 / g, with a lateral impact strength of 34N. The catalyst composition is shown in Table 1. The obtained catalyst was loaded into a single-tube fixed-bed reactor and evaluated; the catalytic performance is shown in Table 2.
[0083] Comparative Example 3
[0084] 1000g of ammonium heptamolybdate was dissolved in 2000g of deionized water at 60℃ to obtain solution A. 460g of bismuth nitrate, 554g of ferric nitrate, 242g of cobalt acetate, 182g of magnesium nitrate, 82g of cesium nitrate, 69.4g of manganese acetate tetrahydrate, and 20.6g of lanthanum nitrate hexahydrate were dissolved in 1840g of 5% dilute nitric acid aqueous solution at 60℃ to obtain dispersion system B. Dispersion system B was added dropwise to solution A. The slurry was stirred and matured at 60℃ for 4 hours. The resulting slurry was then subjected to vacuum distillation in a rotary evaporator at 140℃ to remove the solvent components. Other operations were the same as in Example 3. The catalyst bulk density was 0.97g / cm³. 3 Its specific surface area is 14.9 m². 2 / g, with a lateral impact strength of 28N. The catalyst composition is shown in Table 1. The obtained catalyst was loaded into a single-tube fixed-bed reactor and evaluated; the catalytic performance is shown in Table 2.
[0085] Table 1 Composition of each catalyst
[0086] catalyst Catalyst composition Example 1 Mo 12 Bi1Fe2Co 5.8 La 0.2 Mn 0.4 Cs 0.4 Mg 0.5 O x ]]> Example 2 Mo 12 Bi 1.5 Fe1Co 5.0 La 0.3 Mn 0.2 Cs 0.6 Mg1O x ]]> Example 3 Mo 12 Bi2Fe 2.9 Co 2.1 La 0.1 Mn 0.6 Cs 0.9 Mg 1.5 O x ]]> Example 4 Mo 12 Bi3Fe 1.5 Co 3.5 La 0.1 Ni 1.6 Rb 1.8 Mg 1.6 O x ]]> Example 5 Mo 12 Bi 2.3 Fe 2.9 Co 2.6 Ce 0.2 Ni 0.5 Rb 1.3 Mg 0.9 O x ]]> Example 6 Mo 12 Bi 3.4 Fe 2.0 Co 1.4 Ce 0.2 Mn 0.6 Ca 2.0 K 0.8 O x ]]> Example 7 Mo 12 Bi 1.0 Fe 1.5 Co 3.7 La 0.5 Mn 0.5 Ca 0.5 K 2.0 O x ]]> Example 8 <![CDATA[Mo 12 Bi1Fe2Co 5.0 The 0.2 Mn 0.4 Cs 0.4 Mg1O x ]]> Comparative Example 1 <![CDATA[Mo 12 Bi1Fe2Co 5.8 La 0.2 Mn 0.4 Cs 0.4 Mg 0.5 O x ]]> Comparative Example 2 <![CDATA[Mo 12 Bi 1.5 Fe1Co 5.0 Day 0.3 Mr 0.2 Cs 0.6 Mg1O x ]]> Comparative Example 3 <![CDATA[Mo 12 Bi2Fe 2.9 Co 2.1 Day 0.1 Mr 0.6 Cs 0.9 Mg 1.5 O x ]]>
[0087]
Example 8
[0088] The catalysts prepared in Examples 1-7 and Comparative Examples 1-3 were used as selective oxidation catalysts for the oxidation of isobutylene / tert-butanol to methacrolein / acid. Catalyst performance was tested at a reaction temperature of 360°C. The catalytic results, analyzed by online gas chromatography, are shown in Table 2. The evaluation methods employed, but were not limited to, the above conditions.
[0089] Table 2 Catalytic performance of the catalyst for the selective oxidation of isobutylene / tert-butanol to methacrolein / acid
[0090]
[0091] The raw materials are tert-butanol, oxygen, nitrogen, and water.
[0092] Using the catalysts prepared in Examples 1-7 of this invention, the conversion rate of isobutylene / tert-butanol in a fixed-bed reactor is 96.0-99.0%, and the selectivity of methacrolein reaches 86.0-89.8%. Under the same conditions, the molybdenum-bismuth oxygen catalyst without the addition of a metal promoter in a complex manner and without pore-expansion treatment exhibits the following catalytic performance: isobutylene / tert-butanol conversion rate of 92.2-95.1% and methacrolein selectivity of 79.6-84.4%. The molybdenum-bismuth oxygen catalyst with the addition of a metal promoter in a complex manner but without pore-expansion treatment exhibits the following catalytic performance: isobutylene / tert-butanol conversion rate of 93.2-97.2% and methacrolein selectivity of 83.7-87.3%. The molybdenum-bismuth oxygen catalyst without the addition of a metal promoter in a complex manner but with pore-expansion treatment exhibits the following catalytic performance: isobutylene / tert-butanol conversion rate of 92.7-96.0% and methacrolein selectivity of 80.7-85.1%. The conversion rate of isobutylene / tert-butanol can be increased by up to 7.7%, the selectivity of methacrolein by up to 7.4%, and the total selectivity of methacrolein and methacrylic acid by up to 5.5%.
[0093] Any numerical value mentioned in this invention, if there is only a two-unit interval between any minimum and any maximum value, includes all values that increase by one unit each time from the minimum to the maximum value. For example, if the amount of a component, or the value of a process variable such as temperature, pressure, or time, is stated as 50-90, in this specification it means specifically listing values such as 51-89, 52-88… and 69-71 and 70-71, etc. For non-integer values, it may be appropriately considered that a unit is 0.1, 0.01, 0.001, or 0.0001. These are merely some specifically specified examples. In this application, in a similar manner, all possible combinations of numerical values between the listed minimum and maximum values are considered to have been disclosed.
[0094] It should be noted that the embodiments described above are only for explaining the present invention and do not constitute any limitation on the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory terms, not limiting terms. Modifications can be made to the present invention within the scope of the claims, and revisions can be made to the present invention without departing from the scope and spirit of the present invention. Although the present invention described herein relates to specific methods, materials, and embodiments, it does not mean that the present invention is limited to the specific examples disclosed herein; on the contrary, the present invention can be extended to all other methods and applications with the same function.
Claims
1. A selective oxidation catalyst for isobutylene / tert-butanol, comprising an active metal component and a promoter metal component, wherein the active metal component comprises Mo, Bi, Fe, and Co, and the promoter metal component comprises at least one selected from rare earth metals, transition metals, alkali metals, and alkaline earth metals; the selective oxidation catalyst for isobutylene / tert-butanol is obtained by mixing, reacting, activating, and pore-expanding an active metal compound and a ligand compound containing the promoter metal compound, wherein... The ligand in the ligand compound containing the auxiliary metal compound is a Schiff base ligand formed by the condensation of 1,3-propanediamine and 2-hydroxy-3-methoxybenzaldehyde, and the pore-expanding agent for the pore-expanding treatment is selected from at least one of dicarboxylic acids and ammonium salts having 2 to 4 carbon atoms.
2. The catalyst according to claim 1, characterized in that, The general formula of the catalyst is: Mo a Bi b Feb c Co d M I e M II f M III g M IV h O x , Among them, M I M is a rare earth metal. II M is a transition metal. III M is an alkali metal. IV It is an alkaline earth metal, a=12, 0 <b<3.5,0<c<3,0<d<8,0≤e<1,0≤f<2,0<g≤2,0<h≤2。 3. The catalyst according to claim 2, characterized in that, M I Selected from at least one of La, Ce, Pr, Nd, Er, Yb, M II Selected from at least one of Mn and Ni, M III Selected from at least one of K, Rb, and Cs, M IV It is selected from at least one of Mg and Ca.
4. A method for preparing the isobutylene / tert-butanol selective oxidation catalyst according to any one of claims 1 to 3, comprising: The catalyst is obtained by mixing and reacting an active metal compound and a ligand compound containing an auxiliary metal compound, activating the mixture, and then performing a pore-expanding treatment.
5. The preparation method according to claim 4, characterized in that, The preparation method specifically includes the following steps: S1. An active metal compound and a ligand compound containing an auxiliary metal compound are added to an acidic liquid medium and mixed to react. After removing the liquid medium, a catalyst precursor is obtained. S2. The catalyst precursor obtained in step S1 is activated by heating to obtain catalyst powder. S3. Add a pore-expanding agent to the catalyst powder obtained in step S2, mix evenly, and then press into shape. S4. After heating to remove the pore-expanding agent, the isobutylene / tert-butanol selective oxidation catalyst is obtained.
6. The preparation method according to claim 5, characterized in that, The active metal compound is selected from at least one of the following: oxides, ammonium salts, nitrates, carbonates, bicarbonates, sulfates, halides, oxalates, acetates, phosphates, hydrogen phosphates, and complexes of active metals; and / or, The auxiliary metal compound is selected from at least one of the following: oxides, ammonium salts, nitrates, carbonates, bicarbonates, sulfates, halides, oxalates, acetates, phosphates, hydrogen phosphates, and complexes of the auxiliary metal; and / or, The ligand compound containing the auxiliary metal compound is a complex formed by the auxiliary metal compound with 1,3-propanediamine and 2-hydroxy-3-methoxybenzaldehyde; and / or, The acid in the acidic liquid medium is selected from at least one of inorganic acids and organic acids; and / or, The solvent in the acidic liquid medium is selected from at least one of water and organic solvents; and / or, In the acidic liquid medium, the mass percentage of acid is 2-15%; and / or, The pore-expanding agent is selected from at least one of diacids and ammonium salts having 2 to 4 carbon atoms; and / or, In step S3, the mass ratio of the pore-expanding agent to the catalyst powder is (2~15):(85~98); and / or, Lubricant is also added in step S3.
7. The preparation method according to claim 6, characterized in that, The active metal compound is selected from at least one of the following: ammonium salts, nitrates, oxalates, acetates, and complexes of active metals; and / or, The auxiliary metal compound is selected from at least one of the following: ammonium salt, nitrate, oxalate, and acetate of the auxiliary metal; and / or, In the ligand compound containing the auxiliary metal compound, the molar ratio of the auxiliary metal compound, 1,3-propanediamine, and 2-hydroxy-3-methoxybenzaldehyde is 1:(1~3):(1~4); and / or, The inorganic acid is selected from at least one of nitric acid, sulfuric acid, hydrochloric acid, and phosphoric acid; and / or, The organic acid is selected from at least one of hydroxycarboxylic acids, monocarboxylic acids, dicarboxylic acids, and tricarboxylic acids; and / or, The solvent in the acidic liquid medium is selected from at least one of water and alcohol; and / or, In the acidic liquid medium, the mass percentage of acid is 5-15%; and / or, The pore-expanding agent is selected from at least one of oxalic acid, ammonium oxalate, ammonium acetate, ammonium carbonate, ammonium bicarbonate, and ammonium bioxalate; and / or, In step S3, the mass ratio of the pore-expanding agent to the catalyst powder is (4~10):(90~96); and / or, The lubricant is selected from at least one of graphite and hydroxysilicates; and / or, The mass ratio of the lubricant to the pore expander is (3~6):(2~10).
8. The preparation method according to claim 7, characterized in that, In the ligand compound containing the auxiliary metal compound, the molar ratio of the auxiliary metal compound, 1,3-propanediamine, and 2-hydroxy-3-methoxybenzaldehyde is 1:(1~2):(1~3); and / or, The inorganic acid is selected from at least one of nitric acid and phosphoric acid; and / or, The organic acid is selected from at least one of acetic acid, citric acid, oxalic acid, lactic acid, malonic acid, succinic acid, maleic acid, fumaric acid, malic acid, adipic acid, tartaric acid, caffeic acid, and ferulic acid; and / or, In step S3, the mass ratio of the pore-expanding agent to the catalyst powder is (4~8):(92~96); and / or, The mass ratio of the lubricant to the pore expander is (4~6):(6~10).
9. The preparation method according to claim 5, characterized in that, Step S1 includes: S1-1. Add a portion of the active metal compound to an acidic liquid medium and heat. S1-2, Add the remaining active metal compound and continue heating to obtain a reaction system containing a precipitate; S1-3. Add a ligand compound containing a auxiliary metal compound to the reaction system; S1-4. After solid-liquid separation, the obtained precipitate is dried to obtain the catalyst precursor.
10. The preparation method according to claim 9, characterized in that, The heating temperature in step S1-1 is 40~80℃; the heating time is 0.1~5 h; and / or, The heating temperature in steps S1-2 is 40~80℃; the heating time is 3~24 h; and / or, The preparation method of the ligand compound containing the auxiliary metal compound in steps S1-3 includes: first, reacting 1,3-propanediamine and 2-hydroxy-3-methoxybenzaldehyde by condensation to obtain a ligand, then adding the auxiliary metal compound to obtain the ligand compound containing the auxiliary metal compound; and / or, The drying conditions in steps S1-4 are drying at 80~150℃ for 6~24 h.
11. The preparation method according to claim 10, characterized in that, The heating temperature in step S1-1 is 50~70℃; the heating time is 3~5 h; and / or, The heating temperature in steps S1-2 is 50~70℃; the heating time is 3~16 h; and / or, The condensation reaction is performed at 40-80°C for 3-6 hours; and / or, The drying conditions in steps S1-4 are drying at 120~150℃ for 12~24 h.
12. The preparation method according to claim 5, characterized in that, The activation process in step S2 includes: increasing the temperature to 240-260°C at a rate of 1-4°C / min, holding at this temperature for 0.5-2 h, continuing to increase the temperature to 260-280°C at a rate of 1-2°C / min, holding at this temperature for 0.5-1 h, continuing to increase the temperature to 280-300°C at a rate of 1-2°C / min, holding at this temperature for 0-0.5 h, and finally increasing the temperature to 300-350°C at a rate of 1-2°C / min, holding at this temperature for 1-3 h; and / or, The specific operation of step S4 is as follows: the molded body is placed in an activation device, heated to 100-250°C at a rate of 0.5-2°C / min, and held at this temperature for 3-6 h. Then, the temperature is further increased to 450-520°C at a rate of 1-3°C / min, and held at this temperature for 2-5 h. After that, the temperature is cooled to room temperature to obtain the catalyst.
13. A selective oxidation catalyst for isobutylene / tert-butanol according to any one of claims 1 to 3, or a selective oxidation catalyst for isobutylene / tert-butanol obtained by the preparation method according to any one of claims 4 to 12, characterized in that, The catalyst has a specific surface area of 5~50 m². 2 / g, bulk density is 0.5~1.8 g / cm³ 3 .
14. The isobutylene / tert-butanol selective oxidation catalyst according to claim 13, characterized in that, The catalyst has a specific surface area of 10~40 m². 2 / g, bulk density is 0.6~1.5 g / cm³ 3 .
15. The isobutylene / tert-butanol selective oxidation catalyst according to claim 14, characterized in that, The catalyst has a specific surface area of 10~30 m². 2 / g, bulk density is 0.7~1.2 g / cm³ 3 .
16. The use of the isobutylene / tert-butanol selective oxidation catalyst according to any one of claims 13 to 15 in the oxidation reaction of isobutylene / tert-butanol to produce methacrolein / acid.
17. A method for producing methacrolein / acid by oxidation of isobutylene / tert-butanol, comprising the step of contacting isobutylene / tert-butanol with the catalyst for the oxidation of isobutylene / tert-butanol to produce methacrolein / acid according to any one of claims 13 to 15 to carry out an oxidation reaction.
18. The method according to claim 17, characterized in that, The conditions for the oxidation reaction include: The reaction temperature is 300~400℃; The reaction time is 1~48 h; The total volumetric space velocity of the raw material is 500~3000 h. -1 ; The pressure is 0.01~0.2 MPa; The molar ratio of isobutylene:oxygen:water in the raw material is 1:(1~5):(2~6), or the molar ratio of tert-butanol:oxygen:water in the raw material is 1:(1~5):(1~5).
19. The method according to claim 18, characterized in that, The total volumetric space velocity of the raw material is 800~2000 h. -1 .
Citation Information
Patent Citations
Composite metal oxide catalyst as well as preparation method and application thereof
CN112675866A
Catalyst for preparing methylacrolein in fixed bed, preparation method and application
CN114425355A
Method for preparing methylacrolein
CN103524312A
Oxide catalyst
CN103619473A
